PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN, DENGAN MEDIASI KEPUTUSAN PEMBELIAN TERHADAP IKAN BANDANG: PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN, DENGAN PERAN KEPUTUSAN PEMBELIAN TERHADAP IKAN BANDANG - M Sobih Almuayyat; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The aim to analyze the effect quality of product product, price on loyalty of customer, with purchase decisions as a variable of mediating. Case study on milkfish customers at the Gresik Fish Auction Market. Study design/methodology/approach: The sample was determined used a purposive of sampling and respondents total 152. The analyzed of data using SEM PLS with SmartPLS 4.0. Findings: that first hypothesis of product quality: it’s a positive and significant effect on customer loyalty; second, price: it’s a positive and significant effect on purchase decisions; third, price: it’s a positive and significant effect on customer loyalty; fourth, purchase decisions it’s a positive and significant effect on customer loyalty; and fifth, price has a positive and significant effect on loyalty of customer mediated by purchase decisions. Originality/value: This research provides empirical evidence that product quality directly forms loyalty in traditional market commodities without needing a complex decision process. It is hoped that the results will be useful for local fish entrepreneurs to formulate effective pricing and quality control strategies.